Meningkatkan Keterampilan Membaca Peserta Didik Kelas Rendah Melalui Media Flashcards - Erlin Putri Anggraeni; Encep Andriana; Siti Rokmanah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
Language skills are important for all individuals, especially in the first grade of elementary school students, reading skills are the main focus. Teachers have an important role in improving the reading skills of learners, and to achieve this, the application of an effective approach becomes very important. This study aims to evaluate the learning strategies used by teachers in improving the reading ability of students in grade 1, as well as identify inhibiting factors in the development of students' reading skills. The method used in this study is descriptive qualitative method, with data collection involving interview and observation techniques. This research was carried out in SD Negeri Cikande 1. The results showed that teachers use various strategies in improving students' reading skills, including spelling, sound, and syllabic strategies as an effective learning approach. In this context, the approach helps learners in understanding and mastering reading skills well. By using this strategy, teachers also use flashcards learning media. Factors that can inhibit students' reading in the classroom are cognitive factors, environmental factors, lack of encouragement from parents, and low interest in reading.